In-situ detection of active sites for carbon-based bifunctional oxygen reduction and evolution catalysis. (20th June 2021) - Haid, Richard W.; Kluge, Regina M.; Schmidt, Thorsten O.; Bandarenka, Aliaksandr S.
Highlights: Electrochemical scanning tunnelling microscopy under oxygen reduction and evolution conditions on graphite surfaces. In-situ identification of active sites. ORR active sites are exclusively found at step and defective sites. OER active sites are dependent on the applied potential. The stability of the carbon surface under OER conditions is unaffected at lower potentials. Abstract: Due to their availability and electrochemical versatility, carbon-based electrodes are becoming an increasingly popular option as electrocatalysts for fuel cells and metal-air batteries. Additionally, they show great potential as bifunctional catalysts for the oxygen reduction and evolution reactions (ORR/OER) in an alkaline medium. However, to compete with state-of-the-art catalysts, the nature of the active sites and the surface stability under reaction conditions need to be understood in depth. Here, we present a principle study on highly oriented pyrolytic graphite (HOPG), evaluating the surface behavior under both ORR and OER conditions in 0.1 M KOH. We use noise analysis in electrochemical scanning tunneling microscopy (n-EC-STM) to monitor and compare ORR and OER active sites with resolution down to the nanoscale. Furthermore, surface degradation can be evaluated during the operation. We find that close to the respective reaction onset, step sites and defects are active for both ORR and OER. Terraces sites are largely inactive and only become involved in the OER at higher potentials. This could imply corrosion of the carbon. However, since the observed surface structures remain unaltered before and after applying the OER in our experiments, we find no clear evidence of surface destruction. These fundamental insights could inspire further research concerning the active sites and stability of carbon-based catalysts as well as carbon support structures, to discover ways to tune the surface activity and stability to the dedicated purpose. Graphical abstract: Image, graphical abstract